1979
DOI: 10.3758/bf03335025
|View full text |Cite
|
Sign up to set email alerts
|

Eye contact and the perception of intelligence

Abstract: The perception of intelligence as a function of nonverbal cues was investigated in college students. Thirty undergraduate psychology majors estimated the GPAs of 20 upper division undergraduates based on their nonverbal behavior during a videotaped, career objectives interview. Significant relationships were found between estimated GPAs and two nonverbal behaviors: duration of eye contact and frequency of eye shifts. These nonverbal behaviors appear to be substantive mediators of the perception of an individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 5 publications
2
22
0
1
Order By: Relevance
“…Eye contact has been found to be a salient nonverbal behavior that has a substantial impact on receivers (Brooks et al, 2001;Hemsley & Doob, 1978;Wheeler et al, 1979). Eye contact has been shown to be differentially perceived when men and women enact the same looking-behaviors: only men have been perceived more positively as the amount of eye contact increased (Aguinis & Henle, 2001;Brooks et al, 2001).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Eye contact has been found to be a salient nonverbal behavior that has a substantial impact on receivers (Brooks et al, 2001;Hemsley & Doob, 1978;Wheeler et al, 1979). Eye contact has been shown to be differentially perceived when men and women enact the same looking-behaviors: only men have been perceived more positively as the amount of eye contact increased (Aguinis & Henle, 2001;Brooks et al, 2001).…”
Section: The Present Studymentioning
confidence: 99%
“…Frequency of eye shifts and duration of eye contact were the only two nonverbal behaviors found to be mediators of the perceptions of an individual's intelligence during an interview (Wheeler et al, 1979). A study by Brooks et al in 2001 found that as eye contact increases, people are perceived as more assertive, dominant, decisive, and aggressive.…”
mentioning
confidence: 99%
“…Human response to others looking at them is generally positive (except if the gaze is threatening or competitive) (Jellison & Ickes, 1974;Kleinke, 1986). Maintaining eye contact during social interactions has been shown to have a range of implications, including being perceived as more attentive (Breed, 1972;Kelly, 1978), intelligent (Wheeler, Baron, Michell, & Ginsburg, 1979), and pleasant (Cook & Smith, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Observers with a low level of self-esteem, however, showed the opposite pattern; low eye-contact durations produced perceptions of higher self-esteem than did high durations. Droney and Brooks (1993) and others (Amalfitano & Kalt, 1977;Brooks et aL, 1986;Napieralski et aL, 1995;Wheeler et aL, 1979;Wiens et aL, 1980) note that eye contact is a dominant nonverbal cue which conveys positive traits like a sense of control, confidence, reduced anxiety, and high self-esteem. The present data suggest that the degree to which these interpretations are made by an observer depend to some extent on the personality of that observer, and that low self-esteem individuals in particular might provide an exception to this generally favorable perception pertaining to maintaining eye contact.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining eye contact in situations such as a job interview is a characteristic that generally creates a favorable impression for an observer (e.g., Wheeler, Baron, Michell, & Ginsburg, 1979;Wiens, Harper, & Matarazzo, 1980). The early studies investigating eye contact as a social variable were correlational; participants view videotapes, photographs, or actual interview situations and then make ratings of the characteristics of the person.…”
mentioning
confidence: 99%